Effectiveness of corticosteroid injections in adhesive capsulitis of shoulder: A meta-analysis. Issue 28 (July 2017) - Wang, Wei; Shi, Mingmin; Zhou, Chenhe; Shi, Zhongli; Cai, Xunzi; Lin, Tiao; Yan, Shigui
Abstract: Background: Primary adhesive capsulitis is mainly characterized by spontaneous chronic shoulder pain and the gradual loss of shoulder motion. The main treatment for adhesive capsulitis is a trial of conservative therapies, including analgesia, exercise, physiotherapy, oral nonsteroidal anti-inflammation drugs, and intra-articular corticosteroid injections. Previously, it was reported that intra-articular corticosteroid lead to fast pain relief and improvement of range of motion (ROM). The objective of this study was to determine whether corticosteroid injections would lead to better pain relief and greater improvement in ROM. Methods: We searched PubMed, Medline, and the Cochrane library. We included 5 articles of the 1166 articles identified. Totally injection group included 115 patients and placebo group included 110 patients. We calculated the weighted mean differences to evaluate the pain relief as the primary outcome. We determined the ROM as the secondary outcome. Study quality was evaluated using the 12-item scale. We also used the criteria of the Grading of Recommendations Assessment, Development and Evaluation to evaluate the quality of evidence. Results: In total, 5 studies were included, 4 of which were randomized clinical trials, with a sample size of 225 patients with adhesive capsulitis of the shoulders. The overall pooled data demonstrated that, compared with placebo as control treatment, intra-articular corticosteroid injections were more effective in reducing the pain score at 0 to 8 weeks, but there was no difference between the injection group and the control group at 9 to 24 weeks. Improvement of ROM in the injection group was greater than that of the control group both at 0 to 8 and 9 to 24 weeks. Conclusions: Intra-articular corticosteroid injections were more effective in pain relief in the short term, but this pain relief did not sustain in the long term. Intra-articular corticosteroid injection resulted in greater improvement in passive ROM both in the short and the long terms.